Xǐhuān xuéxí hànyǔ: Buku Ajar Bahasa Mandarin Berbasis Pendekatan Kontekstual - Nadila Puspita Indria Agustin; Primardiana Hermilia Wijayanti; Lukluk Ul Muyassaroh (JoLLA: Journal of Language, Literature, and Arts, 2021)
Abstract: This research aims to develop aMandarin language textbook based on contextual teaching and learning for students at class X senior high school in semester 2. The Mandarin language textbook entitled 喜欢学习汉语 (Xǐhuān xuéxí hànyǔ) was developed to help students and teachers in overcoming the limitations of teaching materials in learning activities. The development useds Research and Development (R&D) methods with ADDIE models, wich consisted of 5 steps, namely Analysis, Design, Development, Implementation, and then Evaluation. The textbooks were developed regarding the criteria for the development of Mandarin teaching materials. Moreover, the materials were arranged using 7 contextual teaching and learning components, namely Constructivism, Inquiry, Questioning, Learning Community, Modeling, Reflection, and Authentic Assessment adapted to the 2013 curriculum. The material of the textbook is equipped by 拼音 (pīnyīn) and its translated version in Bahasa so that it would be easier for students to read 汉字 (hànzì). In addition, they will also study the Mandarin language by linking the learning material with their daily lives. The results showed that a Mandarin language textbook based on contextual teaching and learning for X class senior high school students in semester 2 is suitable to use in Mandarin language learning activities. Keywords: textbook development, Mandarin language, contextual teaching learning Abstrak: Penelitian ini bertujuan mengembangkan buku ajar bahasa Mandarin berbasis pendekatan kontekstual untuk siswa kelas X SMA semester 2. Buku ajar bahasa Mandarin berjudul 喜欢学习汉语 (Xǐhuān xuéxí hànyǔ) dikembangkan untuk membantu siswa dan guru dalam mengatasi keterbatasan bahan ajar dalam kegiatan pembelajaran. Pengembangan ini menggunakan metode Research and Development (R&D) dengan model ADDIE mencakup 5 langkah yaitu Analysis, Design, Development, Implementation, dan Evaluation. Buku ajar dikembangkan dengan kriteria pengembangan bahan ajar bahasa Mandarin dan materi disusun dengan 7 komponen pendekatan kontekstual yaitu Contructiviismsm, Inquiry, Questioning, Learning Community, Modeling, Reflection, dan Authentic Assessment yang disesuaikan dengan kurikulum 2013. Buku ajar bahasa Mandarin berbasis pendekatan kontekstual yang dikembangkan ini menyajikan materi yang dilengkapi拼音(pīnyīn) disertai terjemahan bahasa Indonesia, sehingga memudahkan siswa membaca 汉字 (hànzì) dan mempelajari materi bahasa Mandarin dengan menghubungkan contoh materi yang didapat ke dalam kehidupan sehari-hari siswa. Hasil dari penelitian ini menunjukkan bahwa buku ajar bahasa Mandarin berbasis pendekatan kontekstual untuk siswa kelas X SMA di semester 2 ini layak digunakan dalam kegiatan pembelajaran bahasa Mandarin. Kata Kunci: pengembangan buku ajar, bahasa Mandarin, pendekatan kontekstual